PENDAMPINGAN PASTORAL PERNIKAHANADAT TOKI PINTU DI MINAHASA - Oba, Monica Erika Gracia; Silvia Shalomnita Deny; Yohan Brek; Keyri Stenavi Tampi; Teddy Lendo (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2025)
Pastoral care is an important aspect of church ministry that aims to provide spiritual and emotional support for individuals or groups facing life challenges, including in the context of marriage. This research focuses on the role of the church in pastoral care for the Toki Pintu culture in Minahasa, a tradition that involves two families in a traditional marriage procession. Although the Toki Pintu culture has important values in maintaining family relationships and preventing inbreeding, in practice it has begun to lose its meaning as a means of strengthening family relationships. This study uses a qualitative approach with ethnographic methods to analyze the impact of pastoral care in Toki Pintu traditional marriage, which involves guidance, strengthening and reconciliation in family life. The results show that pastoral care not only focuses on spiritual aspects, but also strengthens social and cultural values in the community. The Toki Pintu tradition has a significant impact on creating family and community harmony, as well as maintaining healthy relationships between married couples with the support of the extended family and community. The pastoral approach in this context helps couples build a solid home life, integrating the teachings of the Christian faith and local cultural values.